POLA ASUH ORANG TUA TUNGGAL DALAM MENDIDIK AGAMA (ISLAM) (STUDI KASUS DI DESA REJOSARI KECAMATAN KALIKAJAR KABUPATEN WONOSOBO) - Desy Desy (Jurnal Pendidikan Agama Islam, 2015)
This study aims to assess parenting single parents in educating their children: parenting as what is given single parents in teaching religion to their children; what about the psychological impact of children treated as such. Subjects in this study were single parents whether caused due to divorce or death, as many as nine people consisting of three men and six women. The instrument of data collection using the questionnaire and observation sheet. Interviews were conducted to determine the type of parenting that given by single parents and observations conducted to observe the religious activities of children in following the activities of the landfill.The result showed that the majority (80%) of single parents using authoritarian parenting that emphasis on strict discipline without compromise, did not give a clear understanding in giving punishment to the child if the child makes a mistake, and often usea rough tone. The effect on children is that they often follow the activities of TPA (departing from the house to the landfill), but upon arrival at the landfill sometimes of them just playing around anyway (not the Koran), the children reasoned important he left home just for fun parents. They are not happy with the conditions at home because parents often scold even give physical punishment if they disobey his father or mother.